Study of an ultra-low temperature fuel cell waste heat recovery system using thermoelectric generator / Muhammad Saufi Sulaiman - Sulaiman, Muhammad Saufi (2019)
Polymer Electrolyte Membrane (PEM) fuel cells generates electrical power from the exothermic electrochemical reaction between hydrogen and oxygen. The thermal power generated are partly consumed by the fuel cell stack to maintain a suitable thermal environment while the bulk of the heat has to be removed as waste heat. Waste heat recovery is a method in the research on improving fuel and energy utilization of energy systems. For PEM fuel cells, waste heat recovery research is concentrated on high temperature fuel cells using advanced thermodynamic cycles due to the high quality of waste heat. For low temperature fuel cells, such as used in smallscale applications for example a mini fuel cell vehicle, these cycles are not efficient and economical. For low temperature fuel cells, thermoelectric generators (TEG) is a suitable technology to directly convert the low quality waste heat energy to electrical energy. This research explores the fundamental characteristics of a TEG waste heat recovery system for a mini vehicle PEM fuel cell stack that operates at ultra-low waste heat temperature. A system consisting of a 2 kW PEM fuel cell and a single unit of TEG assisted by an air cooled finned heat pipe was developed. A mathematical model of the fuel cell-TEG-heat pipe system based on the thermal resistance network heat transfer analogy was also developed and experimentally validated. The experimental variables were fuel cell power output, waste stream temperature, TEG cooling modes (natural and forced convection) and orientation of the TEG towards the heat flow (normal and parallel flow relative to the TEG surface). The cooling modes were applied to simulate a limited scenario of a vehicle at rest and in motion (20 km/h). The highest TEG voltage and power output of 25.7 mV and 218 mW respectively were obtained via forced convection TEG cooling mode and by orienting the TEG surface normal to the hot air flow from the heat source. The thermal resistance network model was in good agreement with the experimental results. The results positively showed that the combined use of TEG, heat pipe and heat sink on a vehicle could offset the ultra-low waste heat temperature from a PEM fuel cell. Successful characterization of this system and validation of the model would allow the system to be further developed for higher performance and contribute to fuel cell system sustainability